Emergence and development of liberal Islam in Indonesia: a critical evaluation - Solihin, Sohirin Mohammad (IIUM Press, 2009)
This book reveals the emergence of liberal Islam in Indonesia by tracing the root of historical perspective. In fact, liberal thought emerged long before independence where secular Muslims made their efforts to expose their religious understanding in the community. Initially, liberal thought emerged from the secular group, which tried to portray the religion with the use of Western mirror. Secondly, liberal thought was propagated by those Muslim scholars who, even though quite well versed in the teachings of Islam, tried to understand and explain the same with a purely rationalistic approach. They tend to interpret certain religious text with their own judgment ignoring the rules and principles laid down by authority of Muslim scholars.